Analysis of Signal Quality Performance on Telkomsel Providers in Simpang Alahan Mati District, Pasaman Regency - Syaza Ibra Harlin; Dikky Chandra; Firdaus Nursal (International Journal of Wireless And Multimedia Communications, 2024)
The emergence of complaints about the quality of the Telkomsel operator signal such as the received signal is not stable, data access is difficult to connect, and connection failures, so in this study to determine the cause of poor signal quality. Analysis of signal quality was carried out in Simpang Alahan Mati, Pasaman. Analysis was carried out by means of a drive test at the LSK120, LSK174, and LSK030 sites using TEMS Pocket on 3G and 4G networks, by analyzing parameter RSRP, SINR for 4G networks as well as the parameters RSCP and Ec/No to the 3G network. Then the propagation calculation is carried out to compare the value of the received power level measured with the coverage site obtained from the propagation calculation. The signal quality of Telkomsel operators in Simpang Alahan Mati From the measurement results for the 4G network with the average parameter value of RSRP - 102 dBm, and SINR 8 dB. The measurement results on the 3G network with an average value of RSCP parameters -98 dBm and Ec/No -11 dB. From the measurement results based on KPI, it can be seen that the signal quality on the 3G and 4G networks is included in the bad category caused by obstacles in the form of hills and trees from the comparison results of the RSRP and RSCP values measured by the range. site with propagation calculations.